Significance of Glomerular Immune Reactivity in Time Zero Biopsies for Allograft Survival Beyond IgA - Vonbrunn, Eva; Serikova, Sofya; Daniel, Christoph; Amann, Kerstin; Schödel, Johannes; Buchholz, Björn; Ferrazzi, Fulvia; Heller, Katharina; Apel, Hendrik; Büttner-Herold, Maike (Frontiers in Medicine, 2021)
The quality of a renal transplant can influence the clinical course after transplantation. Glomerular immune deposits in renal transplants have been described previously, focussing particularly on IgA and were shown to disappear in most cases without impacting the outcome. Here we describe a cohort of zero-time biopsies with regard to glomerular immune deposits and implications for histomorphology and follow-up. 204 zero-time biopsies was analyzed by immunohistochemistry for glomerular immune deposits. Zero-time and 1-year biopsies were evaluted for histomorphologic changes, which together with clinical and follow-up data were assessed for associations with glomerular immune profiles. Nearly half of the analyzed zero-time biopsies showed glomerular immune deposits with mesangial C3 being most frequent (32.9%), followed by IgA (13.7%) and fullhouse patterns (6.9%). Strong C3 deposits (C3high) were only observed in cadaveric transplants. In the majority of cases immune deposits were undetectable in follow-up biopsies and had no adverse effect on transplant function in follow-up of 5 years. In kidney pairs transplanted to different recipients a strong concordance of immune profiles in both kidneys was observed. Moreover, an association of male donor sex and deceased donor transplantation with the presence of immune deposits was seen. In conclusion, glomerular immune deposits are very frequent findings in zero-time biopsies, which seem to be determined by donor parameters including male sex and deceased donor transplants. They had no adverse impact on transplant function in a 5-year follow-up. Glomerular immune deposits in zero-time biopsies, therefore, seem not to indicate an inferior quality of the transplant.